2016
DOI: 10.1007/s40265-016-0653-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Vaccines: Current Status and Future Prospects

Abstract: Congenital human cytomegalovirus (HCMV) infection can result in in severe and permanent neurological injury in newborns, and vaccine development is accordingly a major public health priority. HCMV can also cause disease in solid organ (SOT) and hematopoietic stem cell transplant (HSCT) recipients, and a vaccine would be valuable in prevention of viremia and end-organ disease in these populations. Currently there is no licensed HCMV vaccine, but progress toward this goal has been made in recent clinical trials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 129 publications
(149 reference statements)
0
70
0
Order By: Relevance
“…As a result, several investigators have suggested including the PC in vaccine designs [112]. However, to date, no phase I trial has been completed with a vaccine containing the PC alone.…”
Section: Development Of An Hcmv Vaccine: Potential Role Of the Pcmentioning
confidence: 99%
“…As a result, several investigators have suggested including the PC in vaccine designs [112]. However, to date, no phase I trial has been completed with a vaccine containing the PC alone.…”
Section: Development Of An Hcmv Vaccine: Potential Role Of the Pcmentioning
confidence: 99%
“…Given the complex natural history of CMV infection, the emerging need to plan the evaluation of candidate vaccines against CMV (which may be given to prevent primary infection and/or to the boost immunity in those with natural infection) would be facilitated by knowledge of the seroepidemiology of CMV around the world. We therefore conducted a systematic literature search to identify the parts of the world that have a relatively high burden of infection with this common virus.…”
Section: Introductionmentioning
confidence: 99%
“…Immunisation against CMV could potentially reduce or prevent CMV disease. Results from a recent phase III HELIOS trial did not demonstrate improvement in overall survival or a reduction in CMV end‐organ disease in CMV‐seropositive HSCT recipients that received ASP0113, a bivalent DNA vaccine that encodes CMV glycoprotein B and phosphoprotein 65 antigens . CSJ148 is a combination of two monoclonal antibodies (LJP538 and LJP539) directed against CMV glycoproteins that has been recently studied in preventing CMV disease in HSCT recipients .…”
Section: Vaccines and Monoclonal Antibodiesmentioning
confidence: 99%